A novel surface plasmon resonance sensor based on a functionalized graphene oxide/molecular-imprinted polymer composite for chiral recognition of l-tryptophan. Issue 57 (19th September 2018) - Xu, Xiaoyan; Zhang, Yi; Wang, Bingfeng; Luo, Lin; Xu, Zhenlin; Tian, Xingguo
Abstract : Novel SPR sensor for chiral recognition ofl -tryptophan using a functionalized graphene oxide/molecularly-imprinted polymer composite as a recognition element. Abstract : Herein, a novel surface plasmon resonance (SPR) sensor based on a functionalized graphene oxide (GO)/molecular-imprinted polymer composite was developed for the chiral recognition ofl -tryptophan (l -Trp). The composite's recognition element was prepared via a facile and green synthesis approach using polydopamine as both a reducer of GO and a functional monomer as well as a cross-linker for molecular imprinting. The composite was characterized via Fourier transform infrared spectroscopy, scanning electron microscopy, X-ray diffraction, and Raman spectroscopy. After attaching the composite onto the gold surface of an SPR chip, the sensor was characterized using contact-angle measurements. The sensor exhibited excellent selectivity and chiral recognition for the template ( i.e., l -Trp). Density functional theory computations showed that the difference in hydrogen bonding between the composite element andl -Trp andd -Trp played an important role in chiral recognition.